Physical activity patterns and cognitive function in elderly women: a cross-sectional study from NHANES 2011–2014 - Wu, Junyu; Qiu, Peng; Liu, Meihan; Yu, Weiqiang; Li, Min; Li, Youqiang (Frontiers in Aging Neuroscience, 2024)
Background Amid the backdrop of global aging, the increasing prevalence of cognitive decline among the elderly, particularly within the female demographic, represents a considerable public health concern. Physical activity (PA) is recognized as an effective non-pharmacological intervention for mitigating cognitive decline in older adults. However, the relationship between different PA patterns and cognitive function (CF) in elderly women remains unclear. Methods This study utilized data from National Health and Nutrition Examination Survey (NHANES) 2011–2014 to investigate the relationships between PA, PA patterns [inactive, Weekend Warrior (WW), and Regular Exercise (RE)], and PA intensity with CF in elderly women. Multivariate regression analysis served as the primary analytical method. Results There was a significant positive correlation between PA and CF among elderly women (β-PA: 0.003, 95% CI: 0.000–0.006, P = 0.03143). Additionally, WW and RE activity patterns were associated with markedly better cognitive performance compared to the inactive group (β-WW: 0.451, 95% CI: 0.216–0.685, P = 0.00017; β-RE: 0.153, 95% CI: 0.085–0.221, P = 0.00001). Furthermore, our results indicate a progressive increase in CF with increasing PA intensity (β-MPA- dominated: 0.16, 95% CI: 0.02–0.09, P = 0.0208; β-VPA-dominated: 0.21, 95% CI: 0.09–0.34, P = 0.0011; β-Total VPA: 0.31, 95% CI: −0.01–0.63, P = 0.0566). Conclusion Our study confirms a positive association between PA and CF in elderly women, with even intermittent but intensive PA models like WW being correlated with improved CF. These findings underscore the significant role that varying intensities and patterns of PA play in promoting cognitive health among older age groups, highlighting the need for adaptable PA strategies in public health initiatives targeting this population.